Tug of war: innate immunity and herpes simplex keratitis - Nguyen, Preston; Jacobs, Betty; Mohanram, Athul; Hammons, Caleb; Xing, Junji (Frontiers in Immunology, 2025)
Herpes simplex keratitis (HSK), caused by herpes simplex virus type I (HSV-1) ocular infection, is a leading cause of visual morbidity worldwide, and although cases of HSK can be managed with current medications, new developments are required to make treatments more effective and satisfactory. Current evidence suggests that corneal scarring and vascularization result from chronic inflammation triggered by HSV-1 antigens. The pathogenesis of HSK remains complex and incompletely understood, but there have been many recent advancements have improved our knowledge of HSV-1 and its interactions with the host immune system, particularly in regard to various signaling pathways and regulators. In this review, we discuss the roles of innate immunity in corneal epithelial cells and innate immune cells, DNA sensors and regulators of DNA sensing pathways in HSK caused by acute and recurrent HSV-1 ocular infection and present potential immune-based therapeutic targets for novel HSK treatments.